In this section, you will learn how to find the general solution to a differential equation, and use the general solution to solve an initial value problem.

In this section, you will learn how to find the general solution to a differential equation, and use the general solution to solve an initial value problem.

\(\dfrac{dy}{dx} = 2x + 1{\quad}y(0) = 3\)

\(y = x^2 + x + 3\)

\(\dfrac{dy}{dx} = 6x - 3{\quad}y(0) = 4\)

\(y = 3x^2 - 3x + 4\)

\(\dfrac{dy}{dx} = 2xy{\quad}y(0) = 3\)

\(y = 3e^{x^2}\)